THE GOLDEN JUBILEE OF THE UFPR NURSING COURSE: WHAT DO WE WANT FOR THE NEXT 50 YEARS? - Figueiredo, Karla Crozeta; Macedo, Laura Christina; Miranda, Fernanda Moura D’Almeida (Cogitare Enfermagem, 2024)
Editorial.